Virtual Games: The Mind and Psychology of Youth - Eshimbayevna, Izaitullayeva Lazokat (International Journal of Formal Education, 2025)
This study examines the effects of virtual games on the minds of young people. Virtual games are common among today's youth and can affect their social, psychological and cognitive development. Games can often be useful for reducing stress, increasing creativity and developing strategic thinking. However, they can also have negative consequences such as aggression, social isolation and poor time management.